The potential of psychiatric outpatient centers to reduce the length of stay in inpatient facilities and the negative impact of COVID-19 on the availability of psychiatric services: the case of Latvia - Taube, Maris (Frontiers in Health Services, 2024)
The move from psychiatric hospitals to community-based care is the goal of policies in many countries. Latvia has attempted to reach this goal by establishing two outpatient centers in Riga. Since 2005, when the first outpatient centers opened, the ability of day clinics to reduce the total length of stay for hospital inpatients has been observed, although using the outpatient centers did not affect the number of patients treated. The open-door inpatient wards of the centers also attracted a new patient group. However, due to the COVID-19 pandemic, the number and length of stay of both outpatients and inpatients at psychiatric hospitals decreased. Therefore, other factors that can affect the move from psychiatric hospital inpatient care to outpatient centers should be further investigated.